The Development of the Low-Cost Carriers in the Australia Indonesia Air Travel Market - Baxter, Glenn; Srisaeng, Panarat (วารสารเพื่อการพัฒนาการท่องเที่ยวสู่ความยั่งยืน, 2022)
The objective of this study was to examine the development of the low-cost carriers (LCCs) in the Australia Indonesia air travel market. The study covers the period 2006 to 2020. The case study found that low-cost carriers (LCCs) have significantly grown their annual inbound and outbound enplaned passengers, and this has had a very favorable impact on the low-cost carriers (LCCs) inbound and outbound passenger market shares. The first low-cost carrier (LCC) to enter the market was Jetstar Airways in 2006. Pacific Blue followed in 2008 and they operated low-cost services in 2009 and 2010. In 2011, Pacific Blue’s business model changed to a full-service network carrier model and the airline was rebranded as Virgin Australia. Indonesia Air Asia-X entered the market in 2010 and they were followed by Citlink Airlines in 2019. In 2020, the low-cost carriers had captured 56.09% of the inbound market with the remaining 43.91% held by the full-service network carriers. Also, in 2020, the low-cost carriers had captured 55.19% of the outbound passenger market, with the remaining 44.81% held by the full-service network carriers. The case study revealed that Jetstar Airways is the largest low-cost carrier participating in the market, followed by Indonesia Air Asia-X, and Citilink Airlines.